Preparation and Characterization of Folated Chitosan/Magnetic Nanocarrier for 5-Fluorouracil Drug Delivery and Studying its Effect in Bladder Cancer Therapy - Sharafaldin Al-Musawi (Journal of Global Pharma Technology, 2016)
Among the vigorous anticancer factors, 5-Fluorouracil (5-FU) has been presented fantastic capability against several types of tumor cells. Chitosan-covered super paramagnetic iron oxide nanoparticles (CS-SPION) were synthesized and applied as a nano-carrier for loading of 5-FU (CS-5-FU-SPION) through a reverse micro emulsion technique. In the final preparation process the nanosystem was folic acid functionalized (FA-CS-5-FU-SPION) for targeted therapy purposes. This nanoformulation was studied towards bladder cancer cell lines. Each size and morphology characteristic was evaluated by zeta sizer, AFM and FESEM. Fluorescence microscopy was used to determining the cell internalization rate of prepared nanosystem. Cell viability and apoptosis were surveyed by MTT assay and flowcytometry method respectively. The data indicated that the prepared FA-CS-5-FU-SPION has spherical shape with 79 ± 13 nm average diameter size and appropriate polydispersity rate. Additionally, the remarkable drug loading efficiency (~73%) was notable. This FA-CS-5-FU-SPION also demonstrated sustained release of 5-FU at 37 ◦C in both phosphate and citrate buffer solutions separately. Then the MTT assay and flow cytometry study indicated significant cell toxicity and apoptosis induction by FA-CS-5-FU-SPION. The results supported the fact that FA-CS-5-FU-SPION had become greatly represented antitumor characteristics. In the other hands no adverse outcome were reported for normal cells. Furthermore, it became proved that the FITC-labeled FA-CS-5-FU-SPION, has an effectively entrance into cancerous cell and stimulate cell death and apoptosis.Keywords: Nanoformulation, Chitosan, 5-Fluorouracil, Magnetic nanoparticle, Bladder cancer.